A comprehensive investigation on Spirulina platensis – Part I: Cultivation of biomass, thermo–kinetic modelling, physico–chemical, combustion and emission analyses of bio–oil blends in compression ignition engine. Issue 3 (June 2021) - Nagarajan, Ramesh; Dharmaraja, Jeyaprakash; Shobana, Sutha; Sermarajan, Arunachalam; Nguyen, Dinh Duc; Murugavelh, Somasundaram
Abstract: The present work involves an investigation of Spirulina platensis bio–oil (SPO) with its engine performance in the compression–ignition engine. Spirulina platensis biomass was successfully cultivated in standard Zarrouke medium for few decades, hence in this work S. platensis is cultivated in Zarrouke and economic Zarrouke media show the maximum growth rate of 0.30 and 0.29 g/L/d respectively. The calculated average activation energy ( E a ) values are 100.76, 157.21, 153.88, 167.67, 291.38, and 186.60 kJ/mol for Kissinger, Kissinger–Akahira–Sunose, Tang, Flynn–Wall–Ozawa, Friedman, and Coast Redfern (Jander 3D diffusion) models respectively. Friedman model shows highest E a (365.81 kJ/mo1 at α = 0.7) value with more accuracy than others, hence this model is most favored for S. platensis biomass pyrolysis process. Positive ΔG and ΔH values imply that the pyrolysis process follows spontaneity with endothermic nature. A single–stage fixed bed reactor is utilized to extract SPO with 20% yield at 600 °C and its characterized by physico–chemical, spectral (GC–MS & FTIR), elemental, heat of vaporization, Reid vapor pressure, dynamic viscosity and surface tension methods. Engine performance and emission analysis were performed 5% and 10% SPO blends with 0.50:4.75:4.75 and 1:4.50:4.50 (SPO: Ethanol: Diesel) ratio, respectively under 25%, 50%, 75% and 100% load conditions. 5% SPO blend shows better brake thermal efficiency with lower brake specific fuel consumption values than 10% blend. Furthermore, the emissions of HCs, (NO)x and smoke are slightly higher in SPO blends than diesel. Graphical Abstract: ga1 Highlights: Spirulina platensis – a green microalga effectively drives the bioenergy sector. Economic Zarrouke medium shows an admirable growth rate at low–cost. Friedman model shows notable kinetic parameters to biomass pyrolysis process. 5% SPO blend shows remarkable engine performance and combustion properties. 10% SPO blend shows highest HCs and (NO)x emissions in compression ignition engine.